Validity of prescribing indicators for assessing quality of antibiotic use in Australian general practice. (24th October 2016) - Pont, Lisa G.; Morgan, Tessa K.; Williamson, Margaret; Haaijer, Flora M.; van Driel, Mieke L.
Abstract: Objectives: The aim of this study was to assess the validity of a set of European quality indicators for assessing antimicrobial prescribing in Australian General Practice. Methods: A modified UCLA/RAND appropriateness method was used to assess the validity of 30 antimicrobial prescribing indicators. An expert panel of 12 general practitioners scored the validity of each indicator for measuring quality in Australian general practice. Four quality domains were considered: monitoring antibiotic resistance, benefit to individual patients, value for money and value to policymakers. Panel members were also asked to comment on the relevance to the Australian context and proposed benchmarks for each indicator. Key findings: All panel members were in agreement regarding the validity of each indicator in each of the specified domains with exception of the indicator assessing the use of systemic antibiotics for pneumonia. The majority of the indicators and their associated benchmarks were considered valid for assessing quality in Australian General Practice, however, there were differences regarding the quality domain that each indicator was considered valid for. Monitoring quality considering individual patient benefit was the most problematic domain with respect to validity. Conclusions: This study demonstrates the validity of 30 European indicators for assessing quality of antimicrobial prescribing in general practice in a non‐European setting and provides guidance regarding acceptable benchmarks for the indicators. With international concerns regarding misuse of antibiotics and global interest in prescribing quality, valid evidence‐based antimicrobial prescribing indicators and associated benchmarks are an essential tool for assessing prescribing quality.